Development, assessment and comparison of three high-temperature geothermal-driven configurations for power and hydrogen generation: Energy, exergy thermoeconomic and optimization. (27th November 2020) - Cao, Yan; Mihardjo, Leonardus WW; Farhang, Behzad; Ghaebi, Hadi; Parikhani, Towhid
Abstract: The depletion of fossil fuels and environmental issues that have been brought by them make researchers search for alternative energy resources. Geothermal energy as a reliable sustainable resource has significant potential in the mitigation of greenhouse gas and pollution emissions. In this article, three different geothermal-based systems are designed for hydrogen and electricity production. All three configurations used the same low-temperature geothermal energy. The three proposed systems include ORC, APC and KCS system integrated with PEM technology. These systems are analyzed and compared to energy, exergy, thermoeconomic aspects. The net thermal productivity for the PEM-ORC system, PEM-APC system, and PEM-KCS system are respectively 11.89%, 13.46%, and 11.05%. The overall exergy efficiency for the PEM-ORC system, PEM-APC system, and PEM-KCS system are respectively 50.82%, 48.41%, and 49.02%. The hydrogen production rate of three configurations of PEM-ORC, PEM-APC, and PEM-KCS is 4.78 kg/h, 5.154 kg/h and 4.581 kg/h. Besides the total SUCP of the PEM-ORC unit is 76.72 /GJ. The net SUCP of the PEM-APC system is 78.89 /GJ, this value for combined PEM-KCS is 259.9 /GJ. Moreover, a comprehensive sensitivity evaluation is carried out on the system to evaluate the impact of the key variables on the operation of the plant. Then, optimization procedures are conducted for all three systems. Four TOED, EOED, SOED and MOED methods are employed for this purpose. The SOED method decreased the SUCP of the PEM-KSC system significantly about 22%. The MOED enhances the exergy productivity of the PEM-ORC system about 10%. Highlights: Three different geothermal-based configurations are developed and compared. Hydrogen and electricity are the products of these systems. The systems are analyzed and compared from thermodynamic and thermoeconomic aspects. PEM electrolyzer-Absorption power cycle possesses the best performance.